2016
DOI: 10.1007/s10270-016-0539-8
|View full text |Cite
|
Sign up to set email alerts
|

Configuring use case models in product families

Abstract: In many domains such as automotive and avionics, the size and complexity of software systems is quickly increasing. At the same time, many stakeholders tend to be involved in the development of such systems, which typically must also be configured for multiple customers with varying needs. Product Line Engineering (PLE) is therefore an inevitable practice for such systems. Furthermore, because in many areas requirements must be explicit and traceability to them is required by standards, use cases and domain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…We proposed, applied, and assessed a use case-driven configuration approach based on our modeling method (PUM) [22]. The approach supports three activities.…”
Section: Current Resultsmentioning
confidence: 99%
“…We proposed, applied, and assessed a use case-driven configuration approach based on our modeling method (PUM) [22]. The approach supports three activities.…”
Section: Current Resultsmentioning
confidence: 99%
“…PUMConf has been evaluated in an industrial context for which a case study, i.e., STO, and a questionnaire study were reported in [10]. We applied PUMConf to the functional requirements of STO.…”
Section: Discussionmentioning
confidence: 99%
“…PUMConf is the tool support of our configuration approach for use case-driven development, described in a recent research paper [10]. Figure 1 presents an overview of our tool.…”
Section: Tool Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to model variability in use case specifications, we introduced new product line extensions for the Restricted Use Case Modeling method (RUCM) ( Yue et al, 2013 ). We developed a use case-driven configuration approach ( Hajri et al, 2016a( Hajri et al, , 2016b ) based on PUM. Our configuration approach supports guiding stakeholders in making configuration decisions (e.g., checking consistency of a decision with prior decisions) and automatically generating PS use case models from the PL models and configuration decisions.…”
Section: Introductionmentioning
confidence: 99%